Student perception on the impact of the Livescribe smartpen as an accommodation - Tucker, Lauren; Zamfir, Bogdan (Universal Access in the Information Society, 2021)
The goal of this exploratory qualitative study was to determine how students with disabilities in higher education are using the Livescribe smartpen in their note-taking process and the perceived impact on their academic tasks. Based on participant interviews, many are using the Livescribe smartpen for recording class lectures while taking notes and for engaging with the content outside of the class session. All but one participant reported a perceived positive impact from the use of the Livescribe pen. The positive impacts included improved focus, higher academic outcomes, independence, and capturing complete notes. One unexpected trend that was revealed is that the majority of the participants adjusted their use of the Livescribe smartpen accommodation based on the professor’s teaching style and course structure. © 2021, The Author(s), under exclusive licence to Springer-Verlag GmbH Germany, part of Springer Nature.
1 citations (Crossref) [2023-10-31] Type: Article tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85103414669
Keywords: Course structure; Higher education; Information science; Information systems; Note taking; Qualitative study; Software engineering; Student perceptions; Teaching styles; dept.sed; peer-reviewed